Práctica de valores y convivencia escolar en estudiantes del tercer grado de secundaria de la Institución Educativa N° 64479 Pastor Valencia Peña Ramón Castilla 2025 - Bento Alexandrez, Hosni Vilmar (2025)
The objective of this research is to determine the relationship between the practice of values and school coexistence in third grade of secondary school of Educational Institution No. 64479 Pastor Valencia Peña Ramón Castilla 2025. This study is quantitative and is of a relational, correlational and cross sectional design. population totals 82 third grade of secondary school of Educational Institution No. 64479 Pastor Valencia Peña Ramón Castilla 2025 Students. In this research, a census sampling type will be taken. The technique used was the survey and instruments used were a questionnaire, whose validated were validated by three experts with extensive knowledge of the subject. The results to be obtained through Spearman's Rho non-parametric correlation test, showed a correlation coefficient of ρ = 0.665 at a significance level of p<0.05. This means that a moderate, positive and significant relationship between school coexistence and the practice of values. It is concluded that as they demonstrate a higher level of practice of values, they also exhibit a good level of school coexistence.